2022
DOI: 10.1002/hyp.14666
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and replicability of flood models

Abstract: An ensemble model for global floodforecasting and alerting to forecast flood severity daily at sub‐watershedlevel globally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…The accuracy assessment approach and results are discussed in Section 4 followed by concluding remarks and future work in Section 5. [14] reviewed both publicly and privately available global flood models and tools with the general aim to assist stakeholders to better manage and respond to floods. The authors found that existing global flood models not only differ in their forecasting ability and mapping accuracy but also in terms of methodology and applied physics, process representation, resolution, and frequency at which the outputs are updated.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy assessment approach and results are discussed in Section 4 followed by concluding remarks and future work in Section 5. [14] reviewed both publicly and privately available global flood models and tools with the general aim to assist stakeholders to better manage and respond to floods. The authors found that existing global flood models not only differ in their forecasting ability and mapping accuracy but also in terms of methodology and applied physics, process representation, resolution, and frequency at which the outputs are updated.…”
Section: Introductionmentioning
confidence: 99%